DETERMINAN TARIF PAJAK EFEKTIF PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Tanujaya, Kennardi; Valentine, Ivo (Global Financial Accounting Journal, 2020)
The purpose of this study is to analyze the determinants of effective tax rates. Effective tax rates are often associated with tax avoidance activities. Independent variables in research are company size, audit committee, leverage, independent commissioners, inventory intensity, return on asset, audit quality, capital intensity, and institutional ownership. GAAP ETR and Current ETR are the dependent variables in this research. 493 companies listed on the Indonesia Stock Exchange from 2014 to 2018 act as the study population. Sample selection is done using a purposive sampling technique. 216 companies that fulfilled certain criteria are included as samples for the study. Data testing with panel data regression is done to test the hypothesis. Test results conclude that the rate of return on assets and firm size had a significant negative effect, while institutional ownership had a significant positive effect on the two dependent variables, namely GAAP ETR and Current ETR. Leverage has a significant positive effect on GAAP ETR but has no significant effect on Current ETR. Other independent variables, namely audit quality, inventory intensity, audit committee, capital intensity, and independent commissioners do not show any significant effect on GAAP ETR and Current ETR.